Analisis Fenomena Childfree di Masyarakat: Studi Takhrij dan Syarah Hadis dengan Pendekatan Hukum Islam - M. Irfan Farraz Haecal; Hidayatul Fikra; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study is to discuss the child-free phenomenon that is currently growing in the community. This study uses a qualitative approach through the takhrij and syarah hadith methods with an analysis of Islamic law. The results of this study show that the quality of the hadith narrated by Imam an-Nasa'i No. 3175 concerning the recommendation to multiply children based on the takhrij hadith with the status of Sahih bil al-Makna. As for the syarah, the hadith explains the recommendation of marriage for the purpose of multiplying offspring. The discussion of this research explains that child-free is a subject that can be classified as a woman's reproductive rights if the process of giving birth to a child can bring harm, but child-free views if it is due to fear of inability to educate children or due to the desire to achieve a better career, or other reasons that are not based on a state of emergency ('illat), then it is considered not in accordance with Islamic law. This study concludes that child-freedom is makruh which can shift to permissible if there is 'illat according to the perspective of Islamic law. This study recommends that further research be carried out related to child-freedom in the view of Islam with a social science approach.